Capital Structure Analysis Using The Theory of Pecking Order Approach on Usaha Mikro Berkah Collection Production in Surabaya - Sava Nisa Nur Rahma (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Capital structure is very important for optimizing and maintaining the company if the management in the capital structure is not right, it will result in failure in the business of a company. The method used in this study is a qualitative descriptive method and data analysis based on financial report data for the period 2017.2018,2019 as supporting data, to obtain clear and detailed images based on the data and information that has been obtained. The results showed that the optimal capital structure in 2017 resulted in 67%, in 2018 63%, and in 2019 60% was said to be quite good because the increasing debt had no effect on capital itself. Wacc in 2017 produced 5.19%, in 2018 6.16%, and in 2019 6.15% of the results showed positive and did not have a negative impact on the Berkah Collection Micro Business. The pecking order theory explains that the Berkah Collection Micro Enterprises often use internal capital first then use external capital. Umkm actors are advised to make deeper observations so that the capital structure is more optimal to find out the difference between own capital or capital